Preparation and Study the Properties of PVDF/PEO/WO2 Hybrid Nanocomposite Thin Films Prepared by a Spin Coating Method - Bardan , Aseel N.; Abbas , Lamia K. (Iraqi Journal of Physics, 2024)
In this work, using the spin coating method to create polyvinylidene fluoride (PVDF)/polyethylene oxide (PEO) thin films, the effects of nano-tungsten oxide (WO2) doping were investigated. The novelty of this research lies in its investigation of varying weight concentrations of WO2 nanoparticles (NPs) within the composite films. Comprehensive characterization techniques were employed, including structural analysis via X-ray diffraction (XRD), which revealed a clear and prominent peak in the XRD of the PVDF/PEO films, and the films’ polycrystalline nature with tetragonal structures. The grain size was noted to increase with higher WO2 NPs doping. Field emission scanning electron microscopy (FE-SEM) showed hexagonal-like α-phase PVDF crystals and uniform distribution of WO2 NPs. Furthermore, Fourier-transform infrared spectroscopy (FTIR) confirmed the characteristics of PVDF/PEO and identified specific doping compounds, confirming successful incorporation. The optical transmittance spectra unveiled the films’ optical band gap energy, optical transition types, and absorption characteristics, where novelty emerged as the band gap energy significantly increased from 3.0 eV to 3.64 eV with an increased WO2 NPs weight doping percentage, signifying profound electronic structure modifications and potential applications in optoelectronics and sensors.